Archaeological study of Kazakhstan in the works of the researchers of the XVII century – the first half of the XIX century - Zhumashev, R.M.; Murakami, Ya.; Kukushkin, A.I.; Dmitriev, Е.A. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The first information about the archeological monuments of Kazakhstan belongs to the medieval European, Chinese, Arabic, Persian historians, geographers and travelers. From the middle of the XVI century Russian servicemen began the active development of Siberia and neighboring territories. This led to the emergence of a new block of sources about archaeological antiquities. Peter I decrees played an important role. They were pointed at the search of rarities and respect for them, and were instrumental in organizing the first scientific expeditions (G.F. Miller, P.S. Pallas, I.P. Falk, P.I. Rychkov, I.P. Shangin and others). The routes of the expeditions ran through the territory of Kazakhstan. A significant contribution to the study of the region was made by G.I. Spassky, A.I. Shrenk, S.B. Broniewski and others. Thus, by the middle of the XІX century the first notes on archaeological monuments of Central, Northern and Eastern Kazakhstan were collected. They were rather fragmentary and were not obtained as a result of purposeful research, but in large part in passing. The first excavations carried out were intended to the search for valuable objects. In general, in this era the focus of archaeological study was on things and objects found without serious analytical research. There was no method of excavation, and the level of documentation was quite low.
XVII ғ.–XIX ғ. І-жартысындағы зерттеушілердің еңбегіндегі Қазақстанның археологиялық зерттеулері
Археологическое изучение Казахстана в трудах исследователей XVII в. – первой половины XIX в.
Keywords: Kazakhstan; history of study; archeology; scientists; monument